Thu nhận neodim tinh khiết qui mô pilot từ hỗn hợp đi-đim (Pr/Nd) bằng chiết với dung môi PC88A - Nhuận, Hoàng; Đĩnh, Lưu Xuân; Thuận, Lê Bá; Việt, Nguyễn Đình; Sơn, Lê Hải (Vietnam Journal of Chemistry, 2016)
Solvent extraction experiments have been performed to investigate an optimum condition to separate Nd and Pr from chloride solutions using PC88A and IP2082 solvent applying for the pilot scale extraction system of 120 stages. The extraction process bases on the distribution coefficients of Nd were higher than those of Pr and other reasonable conditions. The effect of various parameters, such as equilibrium time, aqueous pH, extractant concentration, chloride ion concentration, organic solvent, and others on the extraction has been discussed. Results indicated that the conditions including the speed of feed solution with 150 g/L concentration of di-dim is 150 mL/min; rate of 20 % PC88A 20 % is 2L/min; 0.1 mL/min of NaOH 4.5 N and 0.2 L/min of HCl 3 N and the balance of extraction process is obtained in 80 hours. In this study, about 50 Kg product of neodymium 99 % concentrate is obtained by the solvent extraction system including 100 stages of extracted separation and scrubing; and 20 stages of tripping. Keywords. Extraction, scrub, trip, di-dim, neodymium, praseodymium.